Chelidonic Acid and Its Derivatives from Saussurea Controversa: Isolation, Structural Elucidation and Influence on the Osteogenic Differentiation of Multipotent Mesenchymal Stromal Cells In Vitro; Biomolecules; Vol. 9, iss. 5 - Avdeeva E. Elena; Shults E. Elvira; Rybalova T. Tatyana; Reshetov Ya. E. Yaroslav Evgenjevich; Porokhova E. Ekaterina; Sukhodolo I. Irina; Litvinova L. S.; Shupletsova V. V. Valeria; Khaziakhmatova O. G.; Khlusov I. A. Igor Albertovich; Gurjev A. M. Artem Mikhaylovich; Belousov M. V. Mikhail Valerievich (2019, 2019)
4-oxo-4H-pyran-2.6-dicarboxylic acid (chelidonic acid, ChA) in the native state and in the complex with calcium [Ca(ChA)(H2O)3], named saucalchelin (CaChA), was isolated from the extract of Saussurea controversa leaves for the first time for the Asteraceae family. The structure of ChA was determined by NMR, MS and confirmed by X-ray analysis of its monomethyl ester, and CaChA was described by IR, ICP-MS, CHN analysis. The yield of ChA and CaChA was 45 mg/g and 70 mg/g of extract, respectively. The osteogenic activity of ChA, n-monobutyl ester of chelidonic acid, and CaChA has been studied in vitro in a 21-day culture of human adipose-derived multipotent mesenchymal stromal cells (hAMMSCs) in a standard nutrient medium without osteogenic supplements. CaChA significantly stimulated the growth of cell mass and differentiation of hAMMSCs into osteoblasts with subsequent mineralization of the culture and it may be a promising substance for accelerating bone tissue regeneration and engineering.